Inhibition of pulp browning and quality maintenance of late peach cultivars - doi: 10.4025/actasciagron.v34i3.13346 - Neves, Leandro Camargo; Tosin, Jéssica Milanez; Silva, Samuel da; Vasconcelos, Leonara Lima de; Roberto, Sérgio Ruffo (Acta Scientiarum. Agronomy, 2011)
The purpose of this study was to identify the effect of delayed storage on the maintenance of the quality and on the control of pulp browning during cold storage of late peach cultivars. The fruit was harvested at the mature-green stage. All cultivars were exposed to temperatures of 20 ± 0.5ºC and 75 ± 3% of moisture in a cold room for 0.24, or 48 hours. Afterwards, the peaches were kept at 0 ± 0.5ºC and 92 ± 3% of R.H. for 28 days. In the end, the yellow pulp cultivars, regardless of temperature and length of delayed storage, did not present signs of internal browning and were of adequate quality for commercialization. When they were not subjected to delayed storage, the white pulp peaches presented pulp browning after 14 days of cold storage plus two days out of the cold room. From the results observed in the analysis of soluble solids, titratable acidity and decay development, these peaches showed an increased level of ripening. In both cultivars, delayed storage for 48 hours resulted in increased ripening and decay. Delayed storage for 24 hours was effective in controlling pulp browning and in maintaining the quality of the white pulp peach cultivars.